The answer would be x^4 -16
Explanation: use the FOIL method.
(x^2 +4)(x^2 -4)= x^4 +4x -4x -16. 4x and -4x cancel each other out. You are left with x^4 -16.
F- irst
O- uter
I- nner
L- ast
*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆**☆*――*☆*――*☆*――*☆
Answer: 3x^3+2x^2-2x+1
Explanation:
x^3 + 2x^3 - x^2 + 3x^2 -3x + x + 8 - 7 = 3x^3+2x^2-2x+1
I hope this helped!
<!> Brainliest is appreciated! <!>
- Zack Slocum
*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆**☆*――*☆*――*☆*――*☆
Answer:
L=15 6/8feet
B=20 feet
Step-by-step explanation: